Controlled Delivery of Ampicillin and Gentamycin from Cellulose Hydrogels and Their Antibacterial Efficiency - Kaplan, Engin; Ince, Tuncay; Yorulmaz, Esma; Yener, Fadile; Harputlu, Ersan; Lacin, Nelisa Turkoglu (AMER SCIENTIFIC PUBLISHERS, 2014)
A comparative investigation has been undertaken to assess gentamycin (GM) and ampicillin (AMP) in vitro drug release behaviour from bacterial cellulose and to evaluate antibacterial activity with respect to prolonged drug release. Bacterial cellulose membranes (BCMs) were synthesized in Hestrin-Scharmm medium by Acetobacter xylinum extracellularly. The water holding capacity of BC membrane was determined as 65.6 +/- 1.6% in PBS. Dry membranes (1 cm(2)) were immersed in 10% ampicillin solution and 5% gentamycin solution, separately. The interactions between BC fibrils and drugs were illustrated via ATR-FTIR analysis. AMP (m/z 372 -> 196, 372 -> 182) and GM (m/z 4783 -> 3223, 4783 -> 1572) release from membranes and drug content of BCM were observed by positive-ion electrospray and detected by multiple reaction monitoring (MRM) with an LC-tandem mass spectrometer (LC/MS/MS). The AMP and GM content in BCM were 99 mg/cm(2) and 48 mg/cm(2), respectively. AMP-BCMs and GM-BCMs released only 0.107% and 0.113% of the loaded drug in the membrane within 24 h respectively, which is a trace amount of the drug content in hyrogels. This means a burst release did not take place. Besides, BCM released 28% and 17% of AMP and GM content within 7 days, respectively. Additionally, due to stable and prolonged drug release, antimicrobial activity against E. coli, E. feacalis, S. aureus, S. epidermidis, P. Aeruginosa were still prevalent for 3 days of the incubation period. The amounts AMP and GM released from the BCM met the dosage ratio reguirement for inhibiting growth of E. coli, E. feacalis, S. aureus, P. Aeruginosa.
Keywords: Wound Healing; Bacterial Cellulose; Gentamycin; Ampicillin; Drug Release; ANTIBIOTICS; EXPERIENCE; DEFECTS; WOUNDS; Cell Biology